Early Urbanism in Europe. The Trypillia Megasites of the Ukrainian Forest-Steppe - Gajdarska, Biserka (2020)
In this book, a team of international authors examines the hypothesis of independent Eastern European urbanism using the evidence gathered from the multi-disciplinary investigation of the Trypillia megasite of Nebelivka